Idiopathic Osteosclerosis of the Jaws in Turkish Subpopulation: Cone-Beam Computed Tomography Findings - NAMDAR PEKİNER, FİLİZ MEDİHA (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: Idiopathic osteosclerosis (IO) was defined as an asymptomatic, incidental radiographic finding of intrabony sclerosis with unknown origin. The purpose of this retrospective study is to evaluate IO distribution, location, relationships and radiographic features by cone beam computed tomography (CBCT) in Turkish subpopulation. Methods: The study group consisted of CBCT images of 279 individuals, 140 females and 139 males aged 20-69. In received images IO distribution, location in the jaws, dental and cortical relationships, shape and internal structure were evaluated. In axial and cross-sections superoinferior (SID), mesiodistal (MDD) and buccolingual (BLD) distances of IO were measured. The data was compared with age groups and gender. Results: Ninety-two IO in 75 individuals were detected with 26.9% distribution rate. There was a higher prevalence in mandible (82.6%) than maxilla (17.4%). The most frequently involved area was posterior mandible (43.4%). No statistically significant difference in the distribution of IO was found between genders (p>0.05). There was a higher prevalence among young group than middle-aged and above middle-aged groups (p=0.026). According to relation of IO with dental roots separate IO (76.1%) was the most frequent relationship. Seven IO (7.6%) were detected as not related with any cortical structure. Mean SID, MOD and BLD were recorded 5.58; 4.80 and 4.18 mm respectively. Conclusion: IO was detected at a high rate in Turkish subpopulation. CBCT was found as an efficient method to evaluate radiographic features, relationships and location of IO within the jaws before surgical and orthodontic operations.
Keywords: Cone beam computed tomography; Osteosclerosis; Jaw; Mandible; Maxilla; PREVALENCE; FREQUENCY